Graphitic carbon nitride as a photovoltaic booster in quantum dot sensitized solar cells: a synergistic approach for enhanced charge separation and injection. Issue 15 (24th March 2016) - Chetia, Tridip Ranjan; Ansari, Mohammad Shaad; Qureshi, Mohammad
Abstract : A binary hybrid composite of g-C3 N4 and ZnO is introduced as a photoanodic material in QDSSC devices and ∼70% improvement in power conversion efficiency is achieved. Abstract : A ∼70% improvement in power conversion efficiency (PCE, η ) is observed for the devices fabricated with a binary hybrid composite of graphitic carbon nitride and zinc oxide nanorods, i.e., (g-C3 N4 –ZnO NR) [ η ≈ 2.43%, for an optimized weight ratio (0.5 : 1)] as compared to the pristine ZnO NR device ( η ≈ 0.65%). Systematic investigations reveal that g-C3 N4 boosts the light harvesting ability of the photovoltaic devices primarily by impeding photo-induced electron interception to the redox couple and injecting electrons into the conduction band of the semiconductor. Electrochemical impedance spectroscopy (EIS) analysis shows a reduced tunneling of photo-induced electrons to the sulfide–polysulfide (S 2− /Sn 2− ) redox shuttle in the case of (g-C3 N4 –ZnO NR) composite devices. Higher recombination resistance ( R k ) indicates that the g-C3 N4 sheet acts as a barrier for photo-induced electron interception at the working electrode/electrolyte interface. Preliminary investigation using steady state and dynamic photoluminescence analyses suggest a similar fact about the photo-induced electron injection from g-C3 N4 sheets to ZnO, contributing to the enhanced light harvesting ability of (g-C3 N4 –ZnO NR) composite devices.